(untitled) (Medico Legal Update, 2021)
Introduction: The upper cervical spine includes the atlas (C1) and Axis (C2). The anatomy of upper two vertebrae is unique from each other. Atlanto-axial articulation is the most unique, mobile segment of spine, which largely depends on ligamentous supports based on integrity of odontoid for its stability. Historically, atlanto-axial subluxation was treated by reduction and fusion of C1-C2 joint. However, High riding vertebral artery precludes the placement of posterior trans-articular screw, which is liable to injury during screw placement. Socomputed tomography scans can be used to evaluate the risk of “high riding” vertebral artery during the management of atlanto-axial subluxation. Hence, anterior trans-articular screw fixation technique avoids the course of high riding vertebral artery. Material and Method: Nine patients underwent NCCT cervical spine with 3-D reconstruction and clinical evaluation of pain was done by recording the VAS score done pre operatively and after surgery. Results: All surgical cohorts underwent anterior C1-C2 fixation with an average follow up for 24 months. All patients were assessed as per fixed protocol of our local hospital guidelines of orthopaedics department. Pain score was clinically evaluated by VAS score before and after surgery yielding 90% excellent result. Conclusion: Anterior Trans-articular C1-C2 screw fixation isa minimally invasive technique with less blood loss, shorter skins car and faster post-operative recovery. It is an appropriate technique for stabilization of Atlanto-Axial instabilities.